Teachers’ Perception on Influence of Social Adjustment on Academic Performance of Students with Mild Mental Retardation in Gombe State Special School - Shehu, Ruqaiya; Gombe, S., Yakubu; Yahaya Z., Ahmed (Kashere Journal of Education, 2021)
This study focused on determining the perception of teachers on influence of social adjustment on academic performance in West African Examinations Council/National Examinations Council (WAEC/NECO) of students with mild mental retardation in Gombe state, with emphasis on special secondary school. Descriptive survey design was adopted for the study. A total population of 37 teachers were used as respondents. Using drop and pick method, data was collected using adapted social adjustment (questionnaire) from Mei- Yin, Huei – Shyong & Cheng-Jung (2000) in Taiwan with 22 items. The instrument was reduced to 18 items. The instrument was validated by 2 experts and reliability was of 0.82 was obtained through Chronbach’s Alfa coefficient determination formula and the original reported reliability is 0.85. Data was analysed using descriptive (frequency, percentage, mean and SD) statistics. The study found that level of academic performance WAEC/NECO of mentally retarded students is moderate in Gombe state special school, while the level of social adjustment on academic performance WAEC/NECO of mentally retarded students was found to be high as perceived by the teachers. The study concludes that the teachers in Gombe state special school are heterogeneous and social adjustment has great influence on academic performance of mentally retarded students. The study recommends that government should make it a policy that, all mentally retarded persons between the ages of 5-7 are subjected to social adjustment programmes which will transit them into formal school system and parents of mentally retarded children should improve their closeness with their children and also build in hope of their rehabilitation.